Virtual knowledge modelling for distributed teams: towards an interactive design approach. (5th February 2008) - Mejia-Gutierrez, Ricardo; Fischer, Xavier; Bennis, Fouad
A distributed framework for knowledge modelling in interactive design will be presented in this article. A multi-agent approach is proposed in order to support distributed partners in the creation of coherent models for engineering analysis. A granular modelling process is proposed to ensure a coherent construction of models and their analysis. It consists of a global and a local analysis based on a networked Product Life Cycle (PLC). A set of 'Tutor Agents' (TA) intends to guide each partner to extract relevant information from his/her technical domain while a 'Standardisation Process' (SP) is performed with supplied information to find potential redundancies. A coherent model is then obtained that is ready to be analysed by traditional inference engines such as optimisation solvers and constraint satisfaction programming. Furthermore, a case will be presented in order to clarify the framework. The results will enable design teams to integrate constraints from throughout the PLC in order to optimise the evolution of design concepts in distributed design.